THE INFLUENCE OF QUALITY OF WORK LIFE ON EMPLOYEE PERFORMANCE WITH COMPENSATION AS A MODERATING VARIABLE - Kiki Farida Farine; Musran Munizu; Kusuma Agdhi Rahwana; Deswita S; Muhammad Saffath Salsibi (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is quantitative research with an explanatory approach which uses a number of previous studies, especially the five studies mentioned above, as the main inspiration in finding novelty in the research being carried out. The data used in this research is primary data distributed to Daihatsu employees spread throughout Indonesia as many as 600 employees which were obtained through distributing online questionnaires containing 4 statements of strongly agree, agree, normal/normal, disagree and strongly disagree. 16 question items consisting of Quality of Work Life, 6 question items for the Employee Performance variable, and 4 question items for the Compensation variable. The data that researchers obtained from Daihatsu employees was analyzed using the smart PLS 4.0 analysis tool. This result in this research show the Quality of Work Life variable can have a positive relationship and have a significant influence on employee performance. This can be proven because the P-Values value is positive and is below the 0.05 level of significance, namely 0.008. This is because good quality of work life can make employees more enthusiastic at work, happy at work, and ultimately can improve employee performance. Apart from that, the second hypothesis in this research can also be proven because the same thing is that the P-Values value is positive and is below the significance level of 0.05, namely 0.000, which is more significant than the direct test of 0.008. This is because compensation can increase the quality of work life because employees work happily, enthusiastically and comfortably, which ultimately increases its influence on employee performance. In this way, the first and second hypotheses in this research can be accepted and proven. Keywords: Quality Work Life, Employee Performance, Compensation